Migration and Remittances in Latin America and the Caribbean : Engines of Growth and Macroeconomic Stabilizers? - Beaton, Kimberly (IMF Working Papers; Working Paper ;, 2017)
Outward migration has been an important phenomenon for countries in Latin American and the Caribbean (LAC), particularly those in Central America and the Caribbean. This paper examines recent trends in outward migration from and remittances to LAC, as well as their costs and benefits. For the home country, the negative impact from emigration on labor resources and productivity seems to outweigh growth gains from remittances, notably for the Caribbean. However, given emigration, remittance flows play key financing and stabilizing roles in Central America and the Caribbean. They facilitate private consumption smoothing, support financial sector stability and fiscal revenues, and help reduce poverty and inequality, without strong evidence for harmful competitiveness effects through shifts in the real exchange rate.